Pre-departure Training for Healthcare Students Going Abroad: Impact on Preparedness. Issue 4 (5th November 2018) - Kironji, A. Gatebe; Cox, Jacob T.; Edwardson, Jill; Moran, Dane; Aluri, James; Carroll, Bryn; Chen, Chi Chiung Grace
Background: Many medical and nursing schools offer opportunities for students to participate in global health experiences abroad, but little is known about the efficacy of pre-departure training in preparing students for these experiences. Objectives: The primary aim was to identify characteristics of pre-departure training associated with participants' reporting a high level of preparedness for their global health experiences. Secondary objectives included identifying students' preferred subjects of study and teaching modalities for pre-departure training. Methods: A questionnaire was distributed to all medical and nursing students at our institution from 2013 to 2015. Questions addressed prior global health experiences and pre-departure training, preferences for pre-departure training, and demographic information. Findings: Of 517 respondents, 55% reported having a prior global health experience abroad, 77% of whom felt prepared for their experience. Fifty-three percent received pre-departure training. Simply receiving pre-departure training was not associated with perceived preparedness, but pre-departure training in the following learning domains was: travel safety, personal health, clinical skills, cultural awareness, and leadership. Perceiving pre-departure training as useful was also independently associated with self-reported preparedness. Students' preferred instruction methods included discussion, lecture, and simulation, and their most desired subjects of study were travel safety (81%), cultural skills (87%), and personal health (82%). Conclusions: Incorporating travel safety, personal health, clinical skills, cultural awareness, and/or leadership into pre-departure training may increase students' preparedness for global health experiences. Student perceptions of the usefulness of pre-departure training is also associated with self-reported preparedness, suggesting a possible "buy-in" effect.